The milk-based diet of infancy and the gut microbiome. (9th August 2019) - Hao, Hu; Zhu, Lixin; Faden, Howard S
Abstract: The composition and the diversity of the gut microbiome play a major role in the health and well-being of humans beginning at birth. The impact of the diet on the structure and the function of the gut microbiome is evident by the changes in the gut microbiome concurrent with the transition from human milk to solid food. Complex oligosaccharides contained in milk are essential nutrients for commensal microbes in the infant gut. The most important commensal bacterium in the infant gut, bifidobacterium, requires α1, 2 fucosylated oligosaccharides for growth. Because not all humans are able to secrete α1, 2 fucosylated oligosaccharides into milk, the gut microbiome of infants and bifidobacteria, in particular, vary considerably between 'secretors' and 'non-secretors'. A paucity of α1, 2 fucosylated oligosaccharides and bifidobacteria in the gut of infants may be associated with poor health.